2007
DOI: 10.7202/016088ar
|View full text |Cite
|
Sign up to set email alerts
|

Étude de l’évolution des déterminants de l’engagement affectif

Abstract: La recherche étudie l’impact des changements apportés dans trois systèmes de GRH sur la variation de l’engagement affectif des employés d’un établissement de santé au Québec entre 1999 et 2002. La problématique de la recherche se base sur la théorie du contrat psychologique de Rousseau (1995), selon laquelle les changements organisationnels modifient les paramètres de la relation d’emploi, lesquels permettent d’améliorer les conditions de travail et le contrat psychologique de l’employé. À l’aide de deux échan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
2
0
6
Order By: Relevance
“…Previous findings about the importance of procedural and distributive justice as predictors of workplace commitment have found that both of them are important predictors of commitment (Meyer et al 2002), but the majority of empirical research has found that procedural justice explains a greater proportion of the variance in commitment (Masterson, Bartol, and Moye 2000; McFarlin and Sweeney 1992). Procedural justice has sufficient weight that some authors even discard distributive justice as an antecedent of organizational commitment, on the grounds that only procedural and interactional justice may predict commitment (Chênevert, Charest, and Simard 2007; Suliman and Kathairi 2013). Our study supports not only the relationship between procedural justice and affective commitment (Harvey and Haines 2005; Lambert et al 2005) but also that of procedural justice and normative commitment (Jamaludin 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings about the importance of procedural and distributive justice as predictors of workplace commitment have found that both of them are important predictors of commitment (Meyer et al 2002), but the majority of empirical research has found that procedural justice explains a greater proportion of the variance in commitment (Masterson, Bartol, and Moye 2000; McFarlin and Sweeney 1992). Procedural justice has sufficient weight that some authors even discard distributive justice as an antecedent of organizational commitment, on the grounds that only procedural and interactional justice may predict commitment (Chênevert, Charest, and Simard 2007; Suliman and Kathairi 2013). Our study supports not only the relationship between procedural justice and affective commitment (Harvey and Haines 2005; Lambert et al 2005) but also that of procedural justice and normative commitment (Jamaludin 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the complexity, Turgut, Tokmak, and Gucel (2012) suggest that affective commitment is directly related to distributive and interactional justice but that normative commitment is related neither to distributive nor procedural justice. Finally, little research has provided support for the relationship between interactional justice and affective commitment (Chênevert, Charest, and Simard 2007; Klendauer and Deller 2009; Suliman and Kathairi 2013; Turgut, Tokmak, and Gucel 2012; Wu and Wang 2008), normative commitment (Leow and Khong 2009; Rego and Souto 2004; Turgut, Tokmak, and Gucel 2012), or continuance commitment (Suliman and Kathairi 2013; Turgut, Tokmak, and Gucel 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comme le soulignent plusieurs auteurs, la perception que se fait l'employé du changement affecte son niveau d'engagement organisationnel (Schalk et Freese, 1997;Chênevert et al, 2007). Ainsi, si ce changement est perçu comme respectant les termes du contrat psychologique, il exercerait un effet positif sur le niveau de l'engagement vis-à-vis de l'organisation.…”
Section: Dans Ce Sens Nous Proposons Queunclassified
“…Les individus étant engagés affectivement à leur organisation adoptent une vision positive envers celle-ci avec une identification forte, un attachement émotif et l'envie de contribuer à l'atteinte des objectifs fixés. Or, l'empowerment a tendance à être considéré comme une condition importante au développement de l'engagement affectif (Chênevert, Charest, & Simard, 2007 ;Thomas & Velthouse, 1990) et des travaux antérieurs ont déjà démontré un lien positif entre le LH et l'EOA (Harris, et al, 2014 ;Hassan, et al, 2013 ;Raub & Robert, 2013). Au regard de chacune des dimensions du LH, l'autonomie et la participation aux prises de décisions ont tendance à être associées positivement à l'EOA de par l'augmentation du contrôle perçu qu'elles induisent (Chênevert et al, 2007 ;Salancik, 1977 ;Spector, 1986).…”
Section: Introductionunclassified
“…Or, l'empowerment a tendance à être considéré comme une condition importante au développement de l'engagement affectif (Chênevert, Charest, & Simard, 2007 ;Thomas & Velthouse, 1990) et des travaux antérieurs ont déjà démontré un lien positif entre le LH et l'EOA (Harris, et al, 2014 ;Hassan, et al, 2013 ;Raub & Robert, 2013). Au regard de chacune des dimensions du LH, l'autonomie et la participation aux prises de décisions ont tendance à être associées positivement à l'EOA de par l'augmentation du contrôle perçu qu'elles induisent (Chênevert et al, 2007 ;Salancik, 1977 ;Spector, 1986). Des travaux antérieurs ont également montré en quoi la confiance des salariés envers leur employeur renforçait leur engagement organisationnel (Campoy & Neveu, 2007).…”
Section: Introductionunclassified